Analisis Pembiayaan Mudharabah dan Musyarakah Terhadap Profitabilitas Bank di BNI Syariah - Fitri Nur Latifah; Dwi Hanifatul Ma’unah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
The purpose of this study is 1) To find out and analyze the influence of mudharabah financing (X1) significantly on bank profitability (Y). 2) To find out and analyze the influence of musharaka financing (X2) significantly on bank profitability (Y) 3) To find out and analyze the influence of mudharabah financing (X1) and musyarakah financing (X) which significantly affect bank profitability (Y).This research uses a quantitative approach to the type of research Explanatory Research. Determination of the sample using purposive sampling was obtained from the 2010-2018 annual financial statements. The independent variable of this study is mudharabah financing (X1) and musyarakah financing (X2), while the dependent variable (Y) is bank profitability. The analysis tool uses multiple linear regression with the help of SPSS software.